Chapter Renaturalization interventions within a regional forest complex located in a costal pine forest In the south of Italy - Ferraro, Francesco (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The spontaneous vegetation of the Alimini district is represented by plant communities that vary in relation to geology and distance from the coastline: garrigue, scrub, scrub forest and Holm Oak forest, reforestation of Pinus halepensis and P. pinea. In the definition of the thinning treatment to be proposed, the identification of the chosen trees for the cutting was done not only based on their vegetational, morphological and phytosanitary features of the single plant, but, primarily keeping in mind the influence exerted by each arboreal element in terms of biospace to the underlying layers.